A Study on English Teaching Standard in Four Agricultural Universities in Bangladesh (The Agriculturists, 2016)
This research has investigated the standard of English teaching in different agricultural universities in Bangladesh. Four agricultural universities namely, Bangladesh Agricultural University, Sher-e-Bangla Agricultural University, Sylhet Agricultural University and Bangabandhu Sheikh Mujibur Rahman Agricultural University were considered in this study conducted in 2015-16. A total of 50 students were selected at random and were interviewed with a pre tested questionnaire. As the medium of instruction of their respective programs, English is a supplementary course in the agricultural universities of Bangladesh which aims to prepare the students to encounter global communication challenges. After the completion of graduation and post-graduation, the students make themselves ready to serve in various local and multinational organizations and companies. In the workplace, English requires additional focuses along with students subjective expertise due to their prime medium of communication in English. In the case of recruitment, employers often suggest them to develop English language proficiency. So, teaching and learning English is worthy, of focus in regard of the agricultural universities. In this study, the researcher has focused on different steps of students academic affiliation with English which includes students academic proficiency in English during admission, needs analysis, syllabus design, purposes of the course as ESP, content quality, hours invested, and assessment. This qualitative research was conducted by observation method and questionnaire survey for data collection. The study revealed that a large number of students studied English course who could communicate efficiently with foreign teams visiting Bangladesh. However, many participants had no clear idea about social and business English. They have suggested the universities to focus on students English proficiency for professional success.The Agriculturists 2016; 14(1) 142-1150